2023
DOI: 10.1007/s11357-023-00930-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the link between water exchange rate across the blood–brain barrier and cognitive performance in normal aging

Valentinos Zachariou,
Colleen Pappas,
Christopher E. Bauer
et al.

Abstract: The blood–brain barrier (BBB) undergoes functional changes with aging which may contribute to cognitive decline. A novel, diffusion prepared arterial spin labeling-based MRI technique can measure the rate of water exchange across the BBB (kw) and may thus be sensitive to age-related alterations in water exchange at the BBB. However, studies investigating relationships between kw and cognition have reported different directions of association. Here, we begin to investigate the direction of associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 109 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…This was mainly associated with microangiopathy, which results in atherosclerosis, narrowing of vessel diameters, and decreased cerebral blood flow (Malojcic et al., 2017; Sabayan et al., 2012; Vicenzini et al., 2007). Vascular sclerosis and chronic under‐perfusion can lead to disruption of the blood–brain barrier (Yang et al., 2017), ultimately manifesting as cognitive and sensorimotor decline and causing cognitive dysfunction (Marshall et al., 2012; Zachariou et al., 2024). Our study revealed a noteworthy association between PI and CSVD total burden and CI, and the predictive value of PI combined with CSVD total burden for CI was higher than that alone; therefore, PI combined with total burden score was clinically used for better prediction of cognitive functioning in CSVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly associated with microangiopathy, which results in atherosclerosis, narrowing of vessel diameters, and decreased cerebral blood flow (Malojcic et al., 2017; Sabayan et al., 2012; Vicenzini et al., 2007). Vascular sclerosis and chronic under‐perfusion can lead to disruption of the blood–brain barrier (Yang et al., 2017), ultimately manifesting as cognitive and sensorimotor decline and causing cognitive dysfunction (Marshall et al., 2012; Zachariou et al., 2024). Our study revealed a noteworthy association between PI and CSVD total burden and CI, and the predictive value of PI combined with CSVD total burden for CI was higher than that alone; therefore, PI combined with total burden score was clinically used for better prediction of cognitive functioning in CSVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other cognitive and neurological disorders have provided evidence that BBB permeability is related to cognitive function [ 19 ]. In Alzheimer’s disease, it has been shown that PS is inversed related to memory and composite cognitive scores and also associated with beta-amyloid and phosphorylated tau concentrations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as a potentially sensitive, non-invasive metric of BBB function, it is important to gain a greater understanding of the interplay between BBB kw and cognition in older adults. A relationship between BBB kw and cognitive performance has been reported ( Gold et al, 2021 ; Shao et al, 2019 ; Uchida et al, 2022 ; Zachariou et al, 2023 ). Specifically, BBB kw has been associated with memory and executive function performance ( Gold et al, 2021 ; Uchida et al, 2022 ; Zachariou et al, 2023 ).…”
Section: Introductionmentioning
confidence: 97%
“…A relationship between BBB kw and cognitive performance has been reported ( Gold et al, 2021 ; Shao et al, 2019 ; Uchida et al, 2022 ; Zachariou et al, 2023 ). Specifically, BBB kw has been associated with memory and executive function performance ( Gold et al, 2021 ; Uchida et al, 2022 ; Zachariou et al, 2023 ). In these studies, higher kw (a greater water exchange rate) and better memory or executive function was observed, although results were region specific and revealed small effects in some cases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation